The influence of concrete strength on the economy of reinforced concrete columns - Abubakar, Aminu Issaka. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1998., 1998)
The effect of increase in strength of concrete on the economy and performance of reinforced concrete columns is investigated. Two different concrete strengths namely 25 and 45 MPa were used to design columns of 16 different buildings with variation in floor panel size and number of stories carried by the column. The study indicates that, improvement on the strength of concrete causes a substantial decrease in the size and / or the reinforcement of columns which in turn lowers the cost of reinforced concrete frames. The decrease in cost ( savings ) is observed to increase with increase in number of stories carried . The cost benefit in reinforced concrete columns from increasing concrete strength decreases as the floor panels get larger.
Keywords: Reinforced concrete.; Reinforced concrete -- Economic aspects.; High strength concrete.; Concrete -- Creep.; Concrete -- Expansion and contraction.